IMPLEMENTATION OF MARKET SERVICE RETRIBUTION POLICY IN BLORA DISTRICT (BLORA KOTA MARKET CASE STUDY) - Liana, Dwi Afri; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2019)
Market Retribution’s Service is the payment service market for the provision of traditional market facilities/ simplified form of stalls, kiosks and grounds are used by traders and by the local government. In this study, the authors chose a case of retribution policy implementation services in the market with case studies Blora Kota Market with first class classification which is located in Blora district administrative center, a strategic location that is not comparable to the income levy within the last five years has increased and decreased sharply. The purpose of this study was to analyze how policy implementation service levies market in Blora analyzed by District Regulation Blora Number 7 of 2010 on Market Retribution’s Service and to analyze the determinants of policy implementation service levies market in Blora analyzed using the theory of policy implementation Merilee S. Grindle. This research is descriptive qualitative method. The result showed that the process of policy implementation in the market services levy with case studies Blora Kota Market is considered not effective, the existing rules in local legislation does not run optimally as collection of levies, classification of tariffs and regions as well as the provision of incentives, implementation of outstanding fees and sanctions, notification of information on the provision of market facilities, classification of traders and tariffs for levies. The determinants of the theory are the type of benefits, extent of change envision, site of decision, program implementer, and resources commited. Recommendations given are the addition of human resources, improvement of quality and capability of officers, increasing the intensity of policy dissemination, enforcement of policies and sanctions, and improvement of damaged market facilities.